Territorial capacity and territorial outcomes: Local governance and municipal NEET rates in Sweden - Tomas Korpi; Renate Minas; Lisa Andersson (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2024)
Youth not in employment, education or training (NEET) is a heterogeneous group in which many run the risk of long-term exclusion from the labor market and from society. Numerous national and international policy initiatives targeting NEETs have therefore been launched, often involving the creation of new programs and the establishment of new governance structures. Little is however known regarding the relationship between these governance structures and NEET rates. This is here explored using unique data on local governance structures in Sweden, data obtained through qualitative surveys with caseworkers in a sample of municipalities strategically selected based on a quantitative analysis of all Swedish municipalities. The results point to the importance of professional knowledge and problem formulation and question the centrality of organizational structures, but also indicate that there may be multiple ways to achieve a particular outcome.
Keywords: H75; H77; H83; I18; I28; I38; J18; 330; Territorial capacity; territorial resources; territorial governance; steering; NEET; local variation; fsQCA